Religious issues during the Period of Imperial Power in Turkestan on the example of Jeffrey Wheeler’s works - Tashkenbaeva, Diyora (The Lingua Spectrum, 2025)
This article examines the complex interactions between Islam and imperial colonial policy in the late 19th and early 20th centuries. It examines how Islam became the basis of local identity and an instrument of resistance to imperial influence. It examines the dual policy of Russian authorities aimed at controlling religious institutions and using Islam to legitimize rule. Particular attention is paid to the role of education in the transformation of religious life, as well as conflicts and cooperation between different religious groups. The article highlights the importance of the work of Geoffrey Wheeler for understanding religious dynamics and cultural processes in Turkestan, which is relevant for contemporary studies of Central Asia.